Jawaharlal Nehru: The Concept of Nationalism: जवाहरलाल नेहरू: राष्ट्रवाद की अवधारणा - Sejwal, Lakshman (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Jawaharlal Nehru aimed to include people from all classes, castes, and religions of society within his concept of nationalism. He believed that true national movements could not achieve success until a sense of national motivation was instilled among the general population of India. This was the reason why he found Mahatma Gandhi’s leadership acceptable and trustworthy, as Gandhi had incorporated people from all sections, castes, religions, and communities of Indian society into the national movement. Working under Gandhi’s leadership, Nehru successfully mobilized Indian farmers, laborers, students, and the general populace to participate in the national movement. Abstract in Hindi Language: जवाहर लाल नेहरू अपने राष्ट्रवाद के अन्तर्गत समाज के सभी वर्गों, जातियों तथा धर्मों के लोगों को सम्मिलित करना चाहते थे। उनका मानना था कि जब तक भारत की सामान्य जनता के अन्दर राष्ट्रीय अभिप्ररेणाएँ पैदा नहीं होगी, तक तक सच्चे अर्थों में राष्ट्रीय आन्दोलन को सफलता की ओर नहीं ले जाया जा सकता है और यही कारण था कि राष्ट्रीय आन्दोलन में महात्मा गान्धी का नेतृत्व उन्हें मान्य तथा विश्वसनीय लगता था, क्योंकि गान्धी ने भारतीय समाज के सभी वर्गों, जातियों, धर्मों तथा सम्प्रदायों के लोगों को अपने राष्ट्रीय आन्दोलन में सम्मिलित किया था। गान्धी के नेतृत्व में कार्य करते हुए वह भारतीय किसानों, मजदूरों, विधार्थियों तथा जनता को राष्ट्रीय आन्दोलन में लाने में सफल रहे। Keywords: भारत, जवाहर लाल नेहरू, राष्ट्रवाद, राष्ट्रीय अभिप्ररेणाएँ।